The Effect Of Free Cash Flow And Managerial Ownership On Debt Policy (Study On Islamic Commercial Banks In Indonesia Registered On The Idx For The 2017–2021 Period) - M. Fauzan Rusyidi Nasution; Kamilah .; Nurwani . (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The study aims to determine the effect of the variables Free cash flow, and Managerial Ownership on Debt Policy (DER) at Islamic Commercial Banks in Indonesia that are liste on the IDX in 2017-2021. This study uses quantitative research. Variable data types are secondary data, namely data obtained from annual financial reports (annual reports) published on the official website of each bank for the 2017-2021 period and also the official websitee of the Indonesia Stoc Exchange. Data analysis technique used in this study includ Descriptiv Statistical Analysis, Classical Assumtion Test, Multiple Linear Regressi Test and Hypothesis Test. The result this study indicate that partially (t test) Free cash flow has a significant positive effect on Debt Policy (DER) with a probability value 0.011 <0.05 while the value of tcount > ttable (2.722 > 2.05183). Partially the variable Managerial Ownership has a significant negative effect on Debt Policy (DER) with a probability value of 0.005 <0.05 while the tcount > ttable (-3.052 > 2.05183). Simultaneously (F test) the Free cash flow and Managerial Owners variables have a significan effect on Debt Policy (DER) with a probability value of 0.001 <0.05 while the value of Fcount > Ftable (9.996 > 3.34). The coefficien of determination is 0.425 or 42.5%.